Can a Digital Book Tracking System Help to Get Books into the Hands of Children? - Khan, Hadi (World Bank, Washington, DC, 2020)
Digital book tracking systems have potential to address some major book supply challenges by providing accurate and easy to access information on the status of books along the supply chain. The evidence from the application of track and trace in Cambodia and a few other countries shows its potential to provide a cost-effective and scalable solution to some major book supply challenges faced by many developing countries. When the right books reach schools and students, the process of teaching and learning to read can begin. Going forward, evaluations of the scale-up of track and trace in Cambodia and of the interventions in Nepal, Niger, and India will yield evidence to inform the design and implementation of book tracking systems in similar country contexts.